Cisplatin, glutathione and the third wheel: a copper-(1, 10-phenanthroline) complex modulates cisplatin–GSH interactions from antagonism to synergism in cancer cells resistant to cisplatin. Issue 10 (12th February 2019) - Vascellari, Sarah; Valletta, Elisa; Perra, Daniela; Pinna, Elisabetta; Serra, Alessandra; Isaia, Francesco; Pani, Alessandra; Pivetta, Tiziana
Abstract : A new drug cocktail is proposed to overcome the cisplatin-resistance due to the presence of glutathione. A2780 cisplatin-resistant cells, treated with the drug cocktail, showed early apoptosis. Abstract : The antagonistic effect of glutathione (GSH) against the cytotoxicity of cisplatin was observed in both wild type and cisplatin-resistant human leukaemia and ovarian carcinoma cell lines. The simultaneous presence of the cytotoxic copper complex [Cu(phen)2 (OH2 )](ClO4 )2 (C0 ) restored the sensitivity of the cells to cisplatin, and, at selected concentrations, led to strong synergistic effects. TheC0 –cisplatin–glutathione system showed a synergistic toxic effect even in the presence of 1000 μM GSH. The three-drug cocktail exerted a higher potency against leukemic cells than against freshly isolated lymphocytes from healthy donors. Compared to actively proliferating normal lymphocytes, leukaemia cells were much more susceptible to the cytocide effect of the three-drug combination and underwent the dying process(es) much faster. When the ovarian carcinoma cells were treated with cisplatin, alone or in combination withC0, late apoptotic effects were mainly observed, suggesting that DNA interactions with theC0 –cisplatin complex trigger a process of programmed cell death. In contrast, the ternary combination induced apoptotic effects similar to that shown byC0 in single treatment, that is, early apoptosis. One possible explanation is thatC0 and cisplatin compete for GSH-binding in the culture medium. GSH in combination withC0 and cisplatin caused a significant induction of the apoptotic process(es), through a pathway which does not compromise the integrity of the plasma membrane of cells.